Awareness on current status of usage of ritonavir in the management of covid among dental students - Jagadheeswari Ramamoorthy; Dhanraj Ganapathy; Kiran Kumar Pandurangan; Nabeel Ahmed; Subhabrata Maiti (Wolters Kluwer Medknow Publications, 2022)
Ritonavir's pharmacodynamics raise questions regarding whether medication concentrations high enough to block the SARS-CoV-2 proteases can be obtained. Ritonavir may have a therapeutic benefit at any stage of the disease, although pharmacodynamic issues and the absence of clinical benefit data among hospitalized COVID-19 patients cast doubt on this claim. To study the awareness on current status of usage of ritonavir in the management of COVID among dental students. This study, which is survey-based, involved a sample of 100 individuals and was carried out on the website Survey Planet. The study included undergraduate and graduate dental students. The dental students were given a questionnaire containing 10 questions. Their responses were gathered. The number and percentage were used to summarize the data. Dental students from Chennai showed adequate knowledge of COVID-19 in the medical environment. Postgraduate students were more aware about the current status of usage of Ritonavir for COVID-19. This study demonstrates the urgent necessity for all health-care workers to regularly implement educational interventions and training program on infection control procedures for COVID-19.